A study of male somatotypes among the South African Bantu mine labourers compared with other groups (Sheldon's nomenclature) - Potgieter, Z. U (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1959.